Free Markets under Siege : Cartels, Politics, and Social Welfare. - Epstein, Richard Allen, 1943- (Hoover Institution Press, 2008)
Drawing on his extensive knowledge of history, law, and economics, Richard Epstein examines how best to regulate the interface between market choice and government intervention?and find a middle way between socialism and libertarianism. He argues the merits of competition over protectionism and reveals the negative results that ensue when political forces displace economic competition with subsidies and barriers to entry. In the process, he provides an illuminating analysis of some of the ways that special interest groups, with the help of sympathetic politicians, have been able to manipulate.